PERILAKU MENGHISAP DARAH NYAMUK ANOPHELES SPP. DI DESA SAKETA, KECAMATAN GANE BARAT, HALMAHERA SELATAN, MALUKU UTARA - Shinta Shinta; Amirullah Baharudin (JURNAL EKOLOGI KESEHATAN, 2019)
ABSTRACT South Halmahera is a malaria-endemic area in Indonesia. One of the efforts to control the vector is to get information on Anopheles spp mosquito bionomics. This study aims to understand the Anopheles spp blood-sucking behavior in Saketa Village, South Halmahera Regency. The study was conducted from May 2013 to April 2014. Catching mosquitoes was carried out from morning to evening using the Human Landing Collection (HLC) method. The results found 9 species of Anopheles namely, An. barbumbrosus, An. farauti, An. kochi, An. indefinitus, An. koliensis, An. punctulatus, An. subpictus, An. tesselatus and An. vagus. The highest Man Hour Density (MHD) is found at an altitude of 25 meters above sea level, namely An. kochi, and An. indefinitus (2.15 and 1.45 mosquitoes/person /hour). MHD at an altitude of 3 masl is dominated by An. kochi and An. indefinitus (1.95, and 1.8 mosquitoes/person/hour). Man Biting Rate (MBR) at an altitude of 25 meters above sea level is dominated by An. kochi and An. indifinitus (25,90 and 17,47 mosquitoes/person/day), at an altitude of 9 masl, dominated by An. punctulatus and An.indefinitus (4,82 and 4,22 mosquitoes/person/day), at an altitude of 3 meters is dominated by An.indefinitus and An. kochi (21.69 and 23.49 mosquitoes/person/day). Anopheles spp. the number of caught at 06.00-07.00 is very low, but the density An. kochi and An. indefinitus increased at 07.00-08.00 and decreased after 17.00. Other Anopheles species remain with low populations throughout capture. Keywords: Anopheles spp., Malaria, Saketa village ABSTRAK Halmahera Selatan merupakan daerah endemis malaria di Indonesia. Salah satu upaya pengendalian vektor adalah mendapatkan informasi bionomik nyamuk Anopheles spp. Penelitian ini bertujuan untuk memahami perilaku menghisap darah Anopheles spp di Desa Saketa, Kabupaten Halmahera Selatan. Penelitian dilaksanakan dari bulan Mei 2013 hingga April 2014. Penangkapan nyamuk dilakukan dari pagi hingga sore hari dengan metode Human Landing Collection (HLC). Hasil penelitian menemukan 9 spesies Anopheles yaitu, An. barbumbrosus, An. farauti, An. kochi, An. indefinitus, An. koliensis, An. punctulatus, An. subpictus, An. tesselatus dan An. vagus. Man Hour Density (MHD) tertinggi ditemukan pada ketinggian 25 mdpl yaitu An. kochi, dan An. indefinitus (2,15 dan 1,45 nyamuk/orang/jam). MHD pada ketinggian 3 mdpl didominasi oleh nyamuk An. kochi dan An. indefinitus (1,95, dan 1,8 nyamuk/orang/jam). Man Biting Rate (MBR) pada ketinggian 25 mdpl didominasi An. kochi dan An. indifinitus (25,90 dan 17,47 nyamuk/org/hari), pada ketinggian 9 mdpl, didominasi oleh An. punctulatus dan An. indefinitus (4,82 dan 4,22 nyamuk/org/hari), pada ketinggian 3 meter didominasi oleh An.indefinitus dan An. kochi (21,69 dan 23,49 nyamuk/org/hari). Anopheles spp. yang tertangkap pada jam 06.00-07.00 jumlahnya sangat rendah, namun kepadatan An. kochi dan An. indefinitus meningkat pada pukul 07.00-08.00 dan menurun setelah pukul 17.00. Spesies Anopheles lainnya tetap dengan populasi yang rendah sepanjang waktu penangkapan. Kata kunci: Anopheles spp., malaria, Desa Saketa